PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Gayatria Oktalina (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
This study is entitled Analysis of the Effect of Cash Turnover and Accounts Receivable Turnover on Profitability. The sample of this research are 13 mining companies listed on the IDX with purposive sampling method. This study uses a quantitative-descriptive method based on financial statement data recorded on the Indonesia Stock Exchange in 2018-2020. Statistical analysis technique used multiple linear regression using SPSS V.23. The results of the study prove that there is an influence of cash turnover on company profitability, there is an influence of accounts receivable turnover on company profitability, and there is an influence between the two variables on company profitability.